Prinsip Ekonomi Syari’ah Pada Pemotongan Gaji ASN Untuk Zakat Profesi di Kanwil Kementerian Agama Kalimantan Barat - Tarmanto, Tarmanto; Iqbal, Ichsan; Luqman, Luqman (LABATILA : Jurnal Ilmu Ekonomi Islam, 2025)
ABSTRACT Not all civil servants who are Muslim at the Regional Office of the Ministry of Religious Affairs of West Kalimantan Province accept the policy of deducting civil servants' salaries for professional zakat, citing management practices that are considered non-transparent and inconsistent with the principles of Islamic economics. This study aims to examine the policy of deducting civil servants' salaries for professional zakat at the Regional Office of the Ministry of Religious Affairs of West Kalimantan Province from the perspective of sharia economic principles, in order to provide a better, more argumentative understanding based on Islamic economic principles regarding the implementation of professional zakat distribution to civil servants. This is a qualitative descriptive study with an Islamic legal and conceptual approach. Data was obtained through in-depth interviews and informant selection through purposive sampling. The results of the study show that the policy of deducting civil servants' salaries for professional zakat is in line with the main principles of Islamic economics, which emphasise justice and public interest as embodied by a leader in making policies. In this case, the policy of deducting salaries for professional zakat is considered capable of accommodating both theocentric and anthropocentric aspects simultaneously. This is evident from the objectives of the policy, which on the one hand is a form of compliance with Islamic law and on the other hand helps civil servants who are confused about how to distribute their professional zakat. In addition, in terms of its impact, this policy is also in accordance with the principles of Islamic economics, because the process is transparent, there are no violations of Islamic law, and no parties are harmed. Keywords: Sharia Economics, Salary Deduction, Principles, Professional Zakat